Nonspherical Nanoparticle Shape Stability Is Affected by Complex Manufacturing Aspects: Its Implications for Drug Delivery and Targeting. Issue 18 (13th August 2019) - Haryadi, Bernard Manuel; Hafner, Daniel; Amin, Ihsan; Schubel, Rene; Jordan, Rainer; Winter, Gerhard; Engert, Julia
Abstract: The shape of nanoparticles is known recently as an important design parameter influencing considerably the fate of nanoparticles with and in biological systems. Several manufacturing techniques to generate nonspherical nanoparticles as well as studies on in vitro and in vivo effects thereof have been described. However, nonspherical nanoparticle shape stability in physiological‐related conditions and the impact of formulation parameters on nonspherical nanoparticle resistance still need to be investigated. To address these issues, different nanoparticle fabrication methods using biodegradable polymers are explored to produce nonspherical nanoparticles via the prevailing film‐stretching method. In addition, systematic comparisons to other nanoparticle systems prepared by different manufacturing techniques and less biodegradable materials (but still commonly utilized for drug delivery and targeting) are conducted. The study evinces that the strong interplay from multiple nanoparticle properties (i.e., internal structure, Young's modulus, surface roughness, liquefaction temperature [glass transition ( T g ) or melting ( T m )], porosity, and surface hydrophobicity) is present. It is not possible to predict the nonsphericity longevity by merely one or two factor(s). The most influential features in preserving the nonsphericity of nanoparticles are existence of internal structure and low surface hydrophobicity (i.e., surface‐free energy (SFE) > ≈55 mN m −1, material–water interfacial tension <6 mN m −1 ), especially if the nanoparticles are soft (<1 GPa), rough ( R rms > 10 nm), porous (>1 m 2 g −1 ), and in possession of low bulk liquefaction temperature (<100 °C). Interestingly, low surface hydrophobicity of nanoparticles can be obtained indirectly by the significant presence of residual stabilizers. Therefore, it is strongly suggested that nonsphericity of particle systems is highly dependent on surface chemistry but cannot be appraised separately from other factors. These results and reviews allot valuable guidelines for the design and manufacturing of nonspherical nanoparticles having adequate shape stability, thereby appropriate with their usage purposes. Furthermore, they can assist in understanding and explaining the possible mechanisms of nonspherical nanoparticles effectivity loss and distinctive material behavior at the nanoscale. Abstract : This report allots valuable guidelines for the design and manufacturing of nonspherical nanoparticles having adequate shape stability, thereby appropriate with their usage purposes . Furthermore, it can assist in understanding and explaining the possible mechanisms of nonspherical nanoparticle effectivity loss in real in vivo conditions and distinctive material behavior at the nanoscale.